(untitled) (Marketing Journal, 2026)
This article examines the relevance of socioeconomic inequality and its impact on many areas. It defines socioeconomic inequality. Statistically, it presents estimates from an analysis of income levels and poverty rates conducted by the National Statistics Committee and the World Bank. A system of government measures based on a comprehensive approach, including the effective implementation of tax, s ocial, budgetary, and investment policies, is considered to reduce inequality.